Evaluasi Penerapan Standar Akuntansi Keuangan EMKM Menggunakan Model CIPP pada UMKM Kota Pekanbaru - Humairoh, Fitri; Ramaiyanti, Sinta; Oktari, Vera; Anggraini, Lila; Khoiriyah, Mayla; Dewi, Nurrahma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study evaluates the implementation of SAK EMKM in MSMEs using the CIPP model approach (Context, Input, Process, Product). The research method employed is qualitative research. The sample and research location consist of 30 MSMEs in Pekanbaru City. Data were collected through semi-structured interviews with the owners or those responsible for financial management. The criteria for selecting MSMEs, using purposive sampling, were businesses that had been operating for at least two years. The findings show that in the context aspect, MSME practitioners have a high awareness of the urgency of financial recording as a vital instrument for monitoring business performance. In the input aspect, limitations in human resources, lack of training, and inadequate recording infrastructure were identified as major obstacles. In the product aspect, positive impacts were found that foster optimism. Thus, it can be concluded that the motivation to adopt SAK EMKM among MSMEs in Pekanbaru is relatively high.